2020
DOI: 10.31234/osf.io/eg9j4
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Are Humans Constantly but Subconsciously Smelling Themselves?

Abstract: All primates, including humans, engage in self-face-touching at very high frequency. The functional purpose or antecedents of this behaviour remain unclear. In this hybrid review we put forth the hypothesis that self-face-touching subserves self-smelling. We first review data implying that humans touch their own face at very high frequency. We then detail evidence from the one study that implicated an olfactory origin for this behaviour: This evidence consists of significantly increased nasal inhalation concur… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 51 publications
(68 reference statements)
0
16
0
Order By: Relevance
“…A self‐odor will inherently be more familiar than that of an unrelated conspecific. Because our animals are single housed and often soil their bedding within their home cages, females serving in this study clearly had prior experience with their own scent (Gallup & Anderson, 2018; Perl et al, 2020). This increased the potential for saturating habituation to their own scent, which might have made self‑other discrimination easier.…”
Section: Discussionmentioning
confidence: 99%
“…A self‐odor will inherently be more familiar than that of an unrelated conspecific. Because our animals are single housed and often soil their bedding within their home cages, females serving in this study clearly had prior experience with their own scent (Gallup & Anderson, 2018; Perl et al, 2020). This increased the potential for saturating habituation to their own scent, which might have made self‑other discrimination easier.…”
Section: Discussionmentioning
confidence: 99%
“…It is also presumed that face touching as a way of self-smelling is largely an unconscious act, for instance, a study in 400 participants, found 94% of them admitted having smelled of themselves [21].…”
Section: Discussionmentioning
confidence: 99%
“…By comparison, the fact that humans are able to extract biological and social cues from body odors has long been dismissed outright (Lundström & Olsson, 2010). Yet, humans permanently produce and process body odors, even if largely on a subconscious level (Perl et al, 2020; Prehn et al, 2006; Zhou & Chen, 2008, 2009). These odors seem to play a role in the perception of self and others and in self-other distinction (Perl et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Yet, humans permanently produce and process body odors, even if largely on a subconscious level (Perl et al, 2020; Prehn et al, 2006; Zhou & Chen, 2008, 2009). These odors seem to play a role in the perception of self and others and in self-other distinction (Perl et al, 2020). Humans can indeed distinguish their own body odor from that of other persons’.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation